LEGAL PROTECTION FOR CONSUMERS IN E-COMMERCE TRANSACTIONS (COMPARATIVE STUDY OF INDONESIA & THAILAND) - Indri Yani Dewi; Padian Adi Salamat Siregar (Sekolah Tinggi Ilmu Hukum Awang Long, 2026)
The development of e-commerce in Indonesia and Thailand presents new challenges in consumer protection that require in-depth comparative studies. Consumers are in a relatively weak position due to limited access to inspecting goods directly, information asymmetry, and the potential risk of fraud and non-conformity of goods. This study analyzes two main research questions: first, how e-commerce transactions are regulated in Indonesia and Thailand; and second, how legal protection for consumers in e-commerce transactions compares in both countries. The research method uses a normative juridical approach with a statute approach and a comparative approach, with a descriptive analytical nature. Data are sourced from primary legal materials in the form of Indonesian and Thai laws and regulations, as well as secondary legal materials in the form of journals and scientific books, which are analyzed qualitatively. The results of the study show fundamental differences between the two countries. Indonesia has a fragmented regulatory system in various regulations, including Law No. 8 of 1999, the ITE Law, and Government Regulation No. 80 of 2019, which creates overlapping authority, applies a limited reverse burden of proof principle that still burdens consumers, and has a dispute resolution system through the BPSK (Regional Consumer Protection Agency) that is time-consuming and has a low level of compliance. In contrast, Thailand implements integrated regulations with the Consumer Protection Act as umbrella legislation, a strict liability principle that benefits consumers by only proving product defects, losses, and causal relationships, and an efficient dispute resolution system through the OCPB and Online Dispute Resolution with a high level of compliance. The existence of the OCPB as a specialized institution with administrative, mediation, and supervisory authority is a strength of the Thai system. The study recommends that Indonesia adopt an integrated approach, strengthen institutions, and develop a technology-based system to improve the effectiveness of e-commerce consumer protection within the context of ASEAN harmonization.